Studi Perbandingan Kinerja Struktur Rangka Bresing Konsentrik Khusus dan Struktur Base Isolation Dengan Analisis Pushover - Suprayitno, Wisnu Edi; Bantot Sutriono; Retno Trimurtiningrum (Universitas Iskandar Muda, 2025)
Earthquakes are phenomena that have the potential to cause damage to building infrastructure, especially high-rise buildings. This condition is an important aspect in the planning of earthquake-resistant buildings, especially related to the use of building structural systems. The purpose of this study was to analyze the response and sismic performance between special concentric braced frame structures and base isolation structures in multi-storey buildings with height variations of 4 floors, 8 floors and 12 floors. Comparative analysis was conducted using ETABS V software.21 with reference to the provisions of the design of earthquake-resistant steel structures. The results of the analysis showed that the deviation between floors and P-Delta effect of base isolation structure is smaller than that of special concentric braced frame structure. From the analysis of pushover, both structures show the level of Life Safety (LS) performance, which means they are still in a safe condition to withstand earthquake loads without experiencing significant damage.